The relationship between CSR and CFP: the lag effect, virtuous circle, and non-linear relationship in this linkage - Liu, Honglin (2018)
This dissertation discusses the relationship between corporate socially responsible and corporate financial performance. I use the UK’s firms as the sample and classify them by Industries. The data across from 2012 to 2017. This dissertation tests three questions and they are (1) the lagged relationship between the two, (2) the virtuous circle in CSR-CFP linkage, and (3) the non-linear relationship in this nexus. Using the GMM-system method to analyze the data, I found the relationship between the two is varied across industries. The lag effect is present in most of the industries. However, the virtuous circle is not stable in Health Care and Telecommunication Industries. The vicious circle presents in Utilities Industry. In addition, the non-linear relationship is detected in the Basic Materials and Telecommunications Industry, but the directions are varied across the different industry.